Efeito do sombreamento na dinâmica e período de controle de plantas daninhas nas culturas da alface e da rúcula em sistema orgânico - Nogueira, Diego Rodrigues Soares (Universidade Federal Rural do Semi-Árido, 2018)
The use of greenhouses that reduce light intensity has been common practice in vegetable crops in the semi-arid region of Brazil because it provides better environmental conditions for the development of crops.This practice also modifies the dynamics of weeds and may alter the interference relationships among weeds and crops. Therefore, the objective of this work was to evaluate the effect of the reduction of the luminosity allowed by the protected environment on the control periods and the dynamics of weeds in the organic crops of lettuce and arugula. For this, two experiments were carried out for each crop in an organic crop property in the municipality of Governador Dix-Sept Rosado-RN, in a randomized complete block design, with three replications. Each experiment corresponded to the cultivation of lettuce or arugula in conditions of full luminosity or in protected environment, with reduction of luminosity in 35 %. The treatments were arranged in a subdivided plot of plots, with the plots coexisting or controlling weeds and as subplots the control/coexistence periods of 0, 7, 14, 21, 28 and 35 days after transplanting (DAT).The log-logistic regression of four parameters was used to determine the critical weed-free period (CWFP), the critical duration of weed interference (CDWI) and the Critical period of weed control (CPWC). Shading altered the dynamics of weeds, with Digitaria horizontalis Willd and Amaranthus spinosus L. being the species with the highest density in both crops and in the uncovered and protected environment, respectively. The absence of weed control reduced lettuce yields by 65.66 and 90.12 %, and 80.01 and 51.69 %, the arugula productivity in the uncovered and protected environment, respectively. The uncovered lettuce CPWC was from 11th to 33rd, from 12th to 28th and from 13th to 22nd DAT, and from arugula from 8th to 29th, from 8th to 26th and from 9th to 22nd DAT, considering reduction of acceptable production of 2.5, 5 and 10 %, respectively.The cultivation in a protected environment reduced the CPWC of the lettuce from 8th to 19th, from 9th to 18th and from 10th to 17th DAT and from arugula to from 20th to 39th, from 20th to 31st and from 21st to 25th DAT considering a reduction of acceptable production of 2.5, 5 and 10 %, respectively. The cultivation of lettuce and arugula in a protected environment, with a 35 % reduction in solar incidence, altered the dynamics of weed species and decreased the weed control period in lettuce and organic arugula
Effect of shading on the dynamics and weed control period in lettuce and arugula crops in organic system
Keywords: Lactuca sativa L.; Eruca sativa Mill.; Competição; Lactuca sativa L.; Eruca sativa L.; Competition; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA